Mechanism of swertiamarin and novel nitrogen-containing metabolites (R)-Gentiandiol and (S)-Gentiandiol in treating non-alcoholic fatty liver disease in rats: an untargeted metabolomics study based on UPLC-Q-TOF/MS - Sun, Yidan; Cui, Fuyan; Tang, Shuhan; Li, Pengyu; Xu, Yaqi; Li, Hao; Wang, Yige; Li, Xintong; Zhang, Minyue; Ma, Rong; Li, Xianna; Xu, Hongying; et al. (Frontiers in Pharmacology, 2025)
Swertiamarin, a predominant iridoid glycoside from hepatoprotective Swertia herbs, is biotransformed in vivo into nitrogen-containing metabolites (R)-gentiandiol and (S)-gentiandiol. These metabolites may be the real active hepatoprotective agents. A high-fat diet-fed rat model was treated for 12 weeks with swertiamarin, (R)-gentiandiol, (S)-gentiandiol and silybin, and the therapeutic effects on non-alcoholic fatty liver disease (NAFLD) were systematically evaluated through biochemical indices and histopathological observations. Swertiamarin and (R)-gentiandiol reversed high-fat diet-induced metabolic disturbances, reduced serum alanine aminotransferase, aspartate aminotransferase, total cholesterol, triglyceride, low-density lipoprotein cholesterol and malondialdehyde, while elevated high-density lipoprotein cholesterol, superoxide dismutase and glutathione peroxidase. However, (S)-gentiandiol exhibited no efficacy. The differential biomarkers in the serum of high-fat diet-fed rats were determined and identified by the metabolomics method combined with multivariate analysis. The results of enrichment analysis showed that NAFLD could be improved by swertiamarin and (R)-gentiandiol by regulating the levels of 21 biomarkers, such as stearic acid, palmitic acid and PC (36:3). According to the pathway enrichment results, swertiamarin and (R)-gentiandiol had potent combined effects in regulating taurine and hypotaurine metabolism, arachidonic acid metabolism, etc. This study is the first verification of the metabolite activity in the NAFLD model, and the dose-dependent effects of (R)-gentiandiol can be used to underscore its central role in swertiamarin’s bioactivity. These findings offer valuable insights to clarify the pharmaceutical material for hepatoprotective effect of Swertia herbs.